Chemoenzymatic Total Synthesis of Sorbicatechol Structural Analogues and Evaluation of Their Antiviral Potential. (19th November 2019) - Sib, Anna; Milzarek, Tobias M.; Herrmann, Alexander; Oubraham, Lila; Müller, Jonas I.; Pichlmair, Andreas; Brack‐Werner, Ruth; Gulder, Tobias A. M.
Abstract: Sorbicillinoids are fungal polyketides characterized by highly complex and diverse molecular structures, with considerable stereochemical intricacy combined with a high degree of oxygenation. Many sorbicillinoids possess promising biological activities. An interesting member of this natural product family is sorbicatechol A, which is reported to have antiviral activity, particularly against influenza A virus (H1N1). Through a straightforward, one‐pot chemoenzymatic approach with recently developed oxidoreductase SorbC, the characteristic bicyclo[2.2.2]octane core of sorbicatechol is structurally diversified by variation of its natural 2‐methoxyphenol substituent. This facilitates the preparation of a focused library of structural analogues bearing substituted aromatic systems, alkanes, heterocycles, and ethers. Fast access to this structural diversity provides an opportunity to explore the antiviral potential of the sorbicatechol family. Abstract : Derivatize and conquer ! Stereoselective oxidative dearomatization with the enzyme SorbC facilitates the chemoenzymatic total synthesis of a focused sorbicatechol library. The library members are assessed for the antiviral properties of this class of natural products against influenza A virus and HIV.